2016
DOI: 10.1177/1471301215570680
|View full text |Cite
|
Sign up to set email alerts
|

Spousal caregivers and persons with dementia: Increasing participation in shared leisure activities among hospital-based dementia support program participants

Abstract: Spousal caregivers of persons with dementia often have difficulty engaging persons with dementia in leisure activities. This qualitative descriptive study identifies how caregivers perceive their spouses' participation in leisure activities since dementia onset and the professional guidance caregivers require to increase persons with dementia participation in shared leisure activities. Nine spousal caregivers from a hospital-based caregiver intervention attended one of three focus groups. Using symbolic intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 51 publications
(64 reference statements)
0
19
0
Order By: Relevance
“…This is disconcerting, considering that barriers to accessing leisure often intensify feelings of exclusion that are already commonly experienced by people who face marginalization (Reid, Frisby, & Ponic, 2002). Much of the exclusion people with dementia experience when it comes to leisure is often related to their discomfort in social settings with others who do not have a dementia diagnosis (Di Lauro, Pereira, Carr, Chiu, & Wesson, 2015;Vikstrom, Josephsson, Stigsdotter-Neely, & Nygard, 2008). Di Lauro and colleagues noted that persons living with dementia are apt to withdraw from social activities when they find social situations too cognitively demanding.…”
Section: Access To and Experiences Of Leisure For Persons With Demementioning
confidence: 99%
See 1 more Smart Citation
“…This is disconcerting, considering that barriers to accessing leisure often intensify feelings of exclusion that are already commonly experienced by people who face marginalization (Reid, Frisby, & Ponic, 2002). Much of the exclusion people with dementia experience when it comes to leisure is often related to their discomfort in social settings with others who do not have a dementia diagnosis (Di Lauro, Pereira, Carr, Chiu, & Wesson, 2015;Vikstrom, Josephsson, Stigsdotter-Neely, & Nygard, 2008). Di Lauro and colleagues noted that persons living with dementia are apt to withdraw from social activities when they find social situations too cognitively demanding.…”
Section: Access To and Experiences Of Leisure For Persons With Demementioning
confidence: 99%
“…For example, Roland and Chappell (2015) reported that spouses often associate negative meanings to leisure activities because these activities produce social anxiety related to feelings of embarrassment. Moreover, recent research has highlighted the difficulty spouses of persons living with dementia experience when it comes to finding leisure pursuits that can be enjoyed as a couple (Di Lauro et al, 2015). Difficulties were related to a reduction in activities that involve cognitive engagement or social interaction.…”
Section: Access To and Experiences Of Leisure For Persons With Demementioning
confidence: 99%
“…Caregiver education is especially important in caring for the elderly [30]. Interventions targeting informal caregivers can improve their knowledge and coping skills, with the result that they are able to take better care of the elderly and experience their caring role more positively [31]. Each older adult and informal caregiver make up a one-to-one group, in which the informal caregiver is considered the supervisor, guardian, partner, assessor, commentator, and prompter of the older adult.…”
Section: Introductionmentioning
confidence: 99%
“…Providing caregivers with education can be a good opportunity for informal caregivers to communicate with others who may have similar caregiving burdens and problems. Feedback from informal caregivers has shown that a dyadic intervention can be a good opportunity for the caregivers to explore activities in which they share an interest with their patient [31]. The Theory of Dyadic Illness Management moves beyond a discussion of the ways in which the individual patient and care partner respond to illness and focuses extensively on the dyad as an interdependent team [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation